Effect of Cryoprotective Media Components on Dog Spermatozoa Viability During - Linnik, T. P.; Egorov, M. I.; Dyubko, T. S.; Belonozhko, A. P. (Problems of Cryobiology and Cryomedicine, 2005)
There was studied the effect of such cryoprotectants (CP) as: glycerol (GL), ethylene glycol (EG), dimethyl sulfoxide (DMSO), N-N-dimethyl formamide (DMF), 1,2-propanediol (1,2-PD) in 1 M concentration on dog spermatozoa (DS) viability before and after freeze-thawing in 3 media, differing by composition. The first medium (TFY) comprised the yolk of chicken eggs, the second one (Ð¢FA) consisted of egg albumin, the third one (Ð¢F) was used without additives. It was established, that the highest viability of DS both before and after cryopreservation was observed under DMF protection in TFA medium. A possible mechanism of egg albumin effect on DS viability in combination with DMF is discussed.